313 RISK FACTORS AND KNOWLEDGE OF SEXUALLY TRANSMITTED DISEASES IN THE NON-REGISTERED FEMALE SEX WORKERS OF CALLAO, PERU. (10th December 2015) - Ramos, M. S.; Zun, J. R.; Montano, S.; Salvatierra, J.
Abstract : Commercial sex continues to play an integral role in the dissemination of sexually transmitted diseases (STD), including human immunodeficiency virus (HIV), to the general population. Governments across the world have taken health outreach measures to reduce STD in commercial sex workers. In Peru, female sex workers (FSW) can register with the Peruvian Ministry of Health to obtain free STD screening tests (including HIV testing) and gynecological examinations, free treatments, and safe sex counseling. In spite of such efforts, an undocumented number of FSW remain unregistered. In this study, we aim to characterize socio-demographics, sexual behaviors, and knowledge of sexually transmitted diseases of non-registered female sex workers. Also, we intend to examine the effectiveness of such governmental health initiatives as applied to the registered female sex workers (FSW) as we compare in Callao, Peru. A one-stage cluster-sample survey was conducted in Callao. Non-registered FSW were interviewed in randomly selected establishments at night time. A total of 45 women with a median age of 27 participated. Our results suggests that the non registered FSW have less recent health check ups and HIV testing, lower STD recognition, and use of condoms compared to registered FSW. In conclusion, this study suggests that public health efforts that target non-registered FSW are needed in Peru and should cover legal information, condom promotion, education, prevention, and medical management of STD.